Locating a Space for Ethics to Appear in Decision-making: Privacy as an Exemplar - Bonner, William (Journal of business ethics, 2007)
Using concepts from Ulrich Beck’s Risk Society, this paper argues that as expertise proliferates questions of ethics in decision-making fall through gaps between domains of expertise. As a consequence, unethical outcomes are unattached to actions taken with no one accountable or responsible for these outcomes. Using Actor-Network Theory (ANT), a case study is presented showing how the sale of students’ personal information by the Calgary Board of Education (CBE) escaped questions of ethics. The sale of student information was the product of the convergence of narrowly focussed technology and education expert actions and decisions with an earlier two-stage translation of privacy from a potential ethical issue to an issue of expert rule creation and interpretation. The purpose of this paper is to show, through an example, how questions of ethics are displaced in expert decision-making and to enable the public, managers, individuals and experts to recognize displacements and, through this, create a space for ethics to appear.